Serbest bölgelerde faaliyette bulunma esasları - Bayraktarbaşı, Müge (My University, 2004)
Soyadı : Müge Bayraktarbaşı letme Uluslararası İşletmecilik Prof. Dr. Doğan Argun Tez Türü ve Tarihi : Yüksek Lisans - Temmuz 2004 Serbest Bölgeler, Faaliyetler, Vergi

SERBEST BÖLGELERDE FAALİYETTE BULUNMA ESASLARI Serbest Bölgeler, ülkenin siyasi sınırları içinde olmakla beraber gümrük hattı dışında sayılan, ülkede geçerli ticari, mali ve iktisadi alanlara ilişkin hukuki ve idari düzenlemelerin uygulanmadığı veya kısmen uygulandığı, sınai ve ticari faaliyetler için daha geniş teşviklerin tanındığı ve fiziki olarak ülkenin diğer kısımlarından ayrılan yerlerdir. Türkiye'de serbest bölgeler gümrük bölgesi dışında sayılır ve gümrük ve kambiyo mükellefiyetlerine dair mevzuat hükümleri bu bölgelerde uygulanmaz. İhracatı arttırmak için yatırımı ve üretimi arttırmak, yabancı sermaye ve teknoloji girişini hızlandırmak, ekonominin girdi ihtiyacını ucuz ve düzenli bir şekilde temin etmek, dış finansman ve ticaret imkanlarından daha fazla yararlanmak amacıyla 1985 yılında 3218 sayılı Serbest Bölgeler Kanunu yürürlüğe girmiştir.Türkiye'de 21 serbest bölge faaliyette bulunmaktadır. 5084 no'lu kanundan önce (06.02.2004) faaliyet ruhsatı almış gerçek ve tüzel kişiler, lisans süreleri sonuna kadar gelir ve kurumlar vergisinden istisnadır. 2009 yılına kadar da her türlü vergi,resim ve harçtan istisnadır. Üretimle uğraşan firmaların gelir ve kurumlar vergisi istisnası mevcut ve yeni kurulacak firmalar için Türkiye'nin AB'ye tam üyeliğine kadar devam edecektir. Serbest bölgelerde Serbest Bölgeler Genel Müdürlüğünden faaliyet ruhsatı almak suretiyle faaliyette bulunulabilir. Serbest bölgelerde T.C.Sosyal Güvenlik Mevzuatı hükümleri uygulanır. Türkiye'den serbest bölgelere sevk edilen mallar dış ticaret rejimine tabi tutulur ve ihraç edilmiş sayılır. Bölgeden Türkiye'ye sevk edilen mallar dış ticaret rejimine tabi tutulur ve ithal edilmiş sayılır. Bölge ile diğer ülkeler ve serbest bölgeler arasında dış ticaret rejimi uygulanmaz. Name and Surname : Müge Bayraktarbaşı Field : Businness Administration Programme : International Businness Supervisor : Proffessor Doğan Argun Degree Awarded and Date : Master - July 2004 Free Zones, Operations, Tax Free Zones are defined as special sites within the country but deemed to be outside of the customs border and they are the regions where the valid regulations related to foreign trade and other financial and economic areas are not applicable, are partly applicable or new regulations are tested in. Free Zones are also the regions where more convenient business climate is offered in order to increase trade volume and export for some industrial and commercial activities as compared to the other parts of country. Turkish free zones are regarded as being outside of the customs territory and legislative provisions pertaining to customs and foreign exchange obligations are not applicable in these zones. With the objective of increasing export-oriented investment and production in Turkey, accelerating the entry of foreign capital and technology, procuring the inputs of the economy in an economic and orderly fashion and increasing the utilization of external finance and trade possibilities, Free Zones Law numbered 3218 was issued in 1985.There are 21 Free Zones have been established in Turkey. The real or legal persons that obtained operating licences before the Law No. 5084 (6.2.2004) came into effect; shall continue to benefit from the exemptions of income or corporate taxes within the limits of the period specified in their operating licences. Shall be exempted from all taxes, levies and duties generated from their activities related to their free zone operations until 2009. Only, the earnings generated from the sales of the goods produced in the zones by the real or legal persons who obtained a production licence on 6.2.2004 or after, are exempted from the income or corporate taxes until the end of the taxation period of the year Turkey becomes full member of the EU. In order to engage in operations in free zones, an Operating Licence have to be obtained from Undersecretariat for Foreign Trade Directorate General of Free Zones. Social security legislation of the Republic of Turkey applies in free zones. Goods that are sent to the zone from Turkey are treated according to the Foreign Trade Regime and are considered exported. Goods forwarded to Turkey from a zone are subject to the Foreign Trade Regime and are considered imported under this legislation. The Foreign Trade Regime does not apply to transactions between a zone and other countries or the transactions among Free Zones.
Keywords: Dış ticaret; Gümrük tarifesi politikası; Serbest Limanlar ve Bölgeler_Türkiye; Serbest ticaret; Ticaret